Business Management Training in The Mina Mandiri Fish Farming Group in Panembangan Village, Cilongok, Banyumas - Dini Siswani Mulia; Restu Frida Utami; Muhammad Muryanto; Eqwar Saputra; Sugeng Priyadi (Altifani Journal: International Journal of Community Engagement, 2024)
The fish feed production business is one of the prospective economic activities. However to support the progress of the business, it is necessary to implement strategies in business management. This activity aims to improve the knowledge and skills of partners in business management, including financial management, bookkeeping, packaging, and digital-based marketing. The partner is the Mina Mandiri pokdakan in Panembangan Village, Cilongok District, Banyumas Regency. The activity method is participatory, with activity stages including socialization, activity implementation, mentoring, and evaluation. The one-group pre-test and post-test methods measure the program's success rate. The results of the PKM activity showed that 83.33% of partner members understood and were able to implement financial management and bookkeeping, 80% of partner members understood and were able to implement packaging, and 85% of partner members understood and implemented digital marketing. All exceeded the target of 80%. Partners already have business bookkeeping that is separated from personal financial reports. Partners also have Shopee and Tokopedia marketplace accounts that can be used for the smooth running of the fish feed production business. The evaluation results show the need for program sustainability to assist partners in overcoming various problems in fish feed production and business management.